2006
DOI: 10.1159/000096423
|View full text |Cite
|
Sign up to set email alerts
|

An Oral Adsorbent, AST-120, Suppresses Oxidative Stress in Uremic Rats

Abstract: Background: The production of reactive oxygen species (ROS) has been suggested to play an important role in the progression of chronic kidney disease (CKD). An oral adsorbent, AST-120, removes uremic toxins such as indoxyl sulfate (IS) and delays the progression of CKD, but the effect on ROS production is unknown. The present study aimed to determine whether AST-120 reduces oxidative stress in uremic rat kidneys using markers of ROS production such as acrolein and 8-hydroxy-2′-deoxyguanosine (8-OHdG). Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 58 publications
0
39
0
Order By: Relevance
“…Furthermore, Nakagawa and colleagues [Nakagawa et al 2006] reported that AST-120 decreased serum creatinine and urinary protein levels, and attenuated histological changes, such as glomerular sclerosis and interstitial fibrosis [Lee et al 2010]. Reduction in serum IL-6, serum creatinine (sCr), estimated glomerular filtration rate and suppressed urinary excretion levels of 8-OHdG and L-fatty acid binding protein, markers of oxidative stress and tubular injury, have also been connected with the administration of AST-120 to patients with uraemia [Nakagawa et al 2006;Nakamura et al 2011].…”
Section: Molecular Mechanisms Of Action Of Ast-120mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Nakagawa and colleagues [Nakagawa et al 2006] reported that AST-120 decreased serum creatinine and urinary protein levels, and attenuated histological changes, such as glomerular sclerosis and interstitial fibrosis [Lee et al 2010]. Reduction in serum IL-6, serum creatinine (sCr), estimated glomerular filtration rate and suppressed urinary excretion levels of 8-OHdG and L-fatty acid binding protein, markers of oxidative stress and tubular injury, have also been connected with the administration of AST-120 to patients with uraemia [Nakagawa et al 2006;Nakamura et al 2011].…”
Section: Molecular Mechanisms Of Action Of Ast-120mentioning
confidence: 99%
“…Several studies reported a positive linear correlation between IS and oxidative biomarker levels, acrolein and 8-hydroxyl-2′-deoxyguanosine, which accelerate progression of uraemia [Nakagawa et al 2006;Fujii et al 2009]. However, one needs to mention that recent literature suggests antioxidant activity of IS against hydroxyl radicals under physiological conditions [Miyamoto et al 2010].…”
Section: Molecular Mechanisms Of Action Of Ast-120mentioning
confidence: 99%
“…All rats underwent five-sixths renal ablation using the method described earlier. 17,19 Eight weeks later, the subtotally nephrectomized rats (age 17 weeks) were divided randomly into two groups (n¼12 in each group): the first group was fed a normal diet (MF; Oriental Yeast, Osaka, Japan) (Nx) and the second group was fed a normal diet containing 0.4 g of AST-120 per 100 g body weight per day (Kureha, Tokyo, Japan) (Nx+AST). Age-matched sham-operated rats fed a normal diet (Sham) were used for comparison.…”
Section: Animal Preparationmentioning
confidence: 99%
“…17 In addition, IS induced free radical production in renal proximal tubular cells 18 and reduced superoxide scavenging activity in the kidneys of normal and uremic rats. 19 We previously showed that endothelial dysfunction was associated with enhanced vascular oxidative and nitrative stress in rats with obesity and renal injury.…”
Section: Introductionmentioning
confidence: 98%
“…An improvement in renal structure and function with AST-120 treatment has been observed in uremic animal models. 116,136,[150][151][152][153] In CKD patients, AST-120 has been shown to improve estimated creatinine clearance, 154 to delay the progression to ESRD, 155 and to improve survival. 156 Two large-scale trials are currently ongoing testing the role of AST-120 in CKD populations.…”
Section: Heartmentioning
confidence: 99%